Evaluation of Class VIII Islamic education Learning Outcomes at SMP 2 Karangtengah Cianjur - Emma Nikmah Sayyidah; Chaerul Rochman; Dindin Jamaluddin (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2019)
This study explains about the evaluation of learning in Islamic Education Class VIII (Eight) at Karangtengah 2 Junior High School Cianjur. The method used in this study is descriptive participatory, the instrument used in this study is about the knowledge aspects of class VIII PAI. Five indicators of the questions contained in the questions given to students are the meaning of the content of QS. Al-Isra verse 27, completes the verse verse QS Al-Isra verse 27, the meaning contained in QS Al-Furqon verse 63, Describing the rules of recitation, it must be compulsory. wisdom contained in the hadith which prohibits excessive use of ablution water. There are two factors that influence children's performance, namely internal and external factors.